The Construction of the Poetic Text in the Dīwān of Ibn al-‘Arandas al-Ḥillī: A Thematic and Artistic Study - Noor Kald Muhyaldeen (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The study “Structure of the poetic text in the collection of Ibn al-Arandas: an objective and artistic study” aims to understand and analyze the poetic structure in the collection of the poet Ibn al-Arandas in an objective and artistic way. The study focuses on analyzing the literary methods and techniques that the poet used in constructing his poems, including rhyme, meter, sentence structures, and use of poetic language. The topic aims to shed light on the artistic aspects that distinguish Ibn al-Arandas’ poetry and how they affect the quality and creativity of poetry. Method: To achieve its objectives, the study relies on an analytical approach that includes a comprehensive review of Ibn al-Arandas’s poetry collection and a deep analysis of a number of his poems. The approach consists of analyzing Ibn al-Arandas's poetic texts in terms of their structure, artistic methods, and their impact on the poetic content. Result: Through this study, it is expected that the results will yield a deeper understanding of the structure of traditional Arabic poetry and how to use poetic techniques to achieve artistic and expressive goals. The results will contribute to enriching the discussion about Arabic poetry and Arabic literature